Faktor–Faktor Yang Mempengaruhi Kesulitan Belajar Peserta Didik Pada Mata Pelajaran Akuntansi Perusahaan Jasa Di Smk Negeri I Bungoro Kabupaten Pangkep - Sahade, Sahade; Rijal, Abd. (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2018)
This study aims to determine the factors that affect student learning difficulties on the subject of accounting services company. The variable of this study is the learning difficulties experienced by students of SMK Negeri 1 Bungoro Pangkep. The type of research used is qualitative research using qualitative descriptive analysis tools and multiple regression analysis. Based on the results of pre-research at SMK Negeri 1 Bungoro concluded that there are several factors that affect students' learning difficulties on accounting services company subjects, based on the minimum completeness criteria (KKM) determined by the school that is 75. The results show that quantitatively, concluded that teachers, learning media tools, facilities and infrastructure, curriculum, time, teaching materials, family, and social environment factors affect learning difficulties in SMK Negeri 1 Bungoro. While the results of regression analysis and hypothesis testing can be concluded that teachers, learning media tools, facilities and infrastructure, curriculum, time, teaching materials, family and social environment are factors that affect learning difficulties learners. All the factors analyzed had positive and significant correlations.This study aims to determine the factors that affect student learning difficulties on the subject of accounting services company. The variable of this study is the learning difficulties experienced by students of SMK Negeri 1 Bungoro Pangkep. The type of research used is qualitative research using qualitative descriptive analysis tools and multiple regression analysis. Based on the results of pre-research at SMK Negeri 1 Bungoro concluded that there are several factors that affect students' learning difficulties on accounting services company subjects, based on the minimum completeness criteria (KKM) determined by the school that is 75. The results show that quantitatively, concluded that teachers, learning media tools, facilities and infrastructure, curriculum, time, teaching materials, family, and social environment factors affect learning difficulties in SMK Negeri 1 Bungoro. While the results of regression analysis and hypothesis testing can be concluded that teachers, learning media tools, facilities and infrastructure, curriculum, time, teaching materials, family and social environment are factors that affect learning difficulties learners. All the factors analyzed had positive and significant correlations.